Pendampingan Gerakan Wanita Sejahtera Taat Pajak dan Upaya Peningkatan Usaha Berbasis Ekowisata - I Gusti Agung Prama Yoga; I Wayan Chandra Adyatma; I Putu Gede Satria Wiraharja (Universitas Warmadewa, 2024)
Indonesia has 3 tax systems, including the Self Assessment System, the Official Assessment System and the Withholding Assessment System. Self assessment is a tax collection system that gives trust and responsibility to taxpayers to take the initiative in registering themselves to obtain a Taxpayer Identification Number (NPWP) and take care of all their tax affairs independently. Starting from calculating, paying and reporting the annual tax return (SPT) itself. Annual personal income tax return (PPh OP) reporting must be carried out every year by taxpayers who have met the objective and subjective requirements no later than (report the OP tax return) at the end of March. Tax Return reporting has been mandated in the Law on General Provisions and Tax Procedures (KUP) article 3, where every taxpayer is required to fill out the tax return correctly, clearly and completely, and for the annual Income Tax Return OP must be submitted no later than 3 months after the tax year ends (WP OP) or no later than 4 months after the tax year ends (Corporate WP). The Prosperous Women's Movement is one of the non-political women's organizations that has a vision of improving women's empowerment. Taxes are mandatory contributions by taxpayers for state development. Women must now be sensitive to the times, educated and willing to learn. The theme of this PkM is smart women who obey taxes. The method used is to socialize taxation and ecotourism business opportunities, discussions, and mentoring. The assistance provided includes the preparation of NIK and NPWP as well as personal tax reporting. Women must have intelligence, because the world is too harsh if it is only devoted to beauty. Our taxes, for us. Wisely fulfilling tax obligations, then the development of the country will continue to develop. Warmadewa University advances the country from education and implements the tri dharma of higher education to prepare quality human resources, ecotourism insights, and global competitiveness.